The Commodity Futures Game : who wins? Who loses? Why? - Teweles, Richard Jack; Harlow, Charles Vendale; Stone, Herbert L. (New York : McGraw-Hill Book Co., 1977)
The book provides invaluable insights into the behavior of futures prices, the element of planned trading, fundamental and technical analysis, and the nature of commodity in futures. The investor is led step-by step to construct a personal trading curve and to understand the implications of the shape of the curve for risk and reward.
Edition for 1969 published under title: The commodity futures trading guide.
Includes index.
Bibliography: p. 333-352.
rua 25/05/17.
Loans.
Keywords: Commodity exchanges; Speculation